A Multilevel Analysis of Stigma and Health: Implications for Research and Policy. (October 2014) - Richman, Laura Smart; Hatzenbuehler, Mark L.
This article reviews research on stigma and discrimination—at both the interpersonal and societal levels—faced by disadvantaged groups. Research on interpersonal discrimination primarily concerns discrimination that is perceived and directly experienced (e.g., discrimination in employment and health care), whereas research on societal discrimination focuses on broad societal factors (e.g., institutional policies, social attitudes). We review evidence across numerous fields of study that rely on several types of research designs, which indicate that both forms of stigma and discrimination demonstrably contribute to health inequalities for disadvantaged groups such as racial and ethnic minorities and lesbian, gay, and bisexual populations. These adverse health outcomes range from maladaptive physiological stress responses in a laboratory setting to premature mortality at a population level. The science on stigma and discrimination applies to policy issues in education, same-sex marriage, and health care delivery. Some current policies increase the experience of stigma. We argue that more holistic social policies can recognize the psychosocial factors that contribute to well-being, thereby reducing social inequalities in health.